1992
DOI: 10.1063/1.352004
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on highly ordered and highly conductive thin films of pentacene

Abstract: Electrical properties of highly ordered and amorphous thin films of pentacene doped with iodineStructural studies on highly conductive thin tlhns of pentacene (PEN) were carried out by x-ray and electron diffraction methods. The ultrathin film before and after doping with iodine was confirmed to consist of single crystalline domains, and the lattice parameters were determined. Drastic elongation along the c axis as a result of doping was observed, while the u-b plane did not change during doping. The intercala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 15 publications
8
87
0
1
Order By: Relevance
“…The results are listed in Table 3. The reciprocal lattice data of the single crystal and the ED results calculated from Minakata et al [7] have been added to this table. Note that the difference between a à and Àa à or b à and Àb à could not be observed.…”
Section: Temperature Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…The results are listed in Table 3. The reciprocal lattice data of the single crystal and the ED results calculated from Minakata et al [7] have been added to this table. Note that the difference between a à and Àa à or b à and Àb à could not be observed.…”
Section: Temperature Dependencementioning
confidence: 99%
“…the stacking of the molecules. The crystal structure and growth of pentacene has been subject of a number of studies [4][5][6][7][8]. Pentacene crystallizes in a layered structure with a herringbone arrangement within the layers (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…50 nm thick. Conductivity measurements on these iodine doped pentacene films revealed that conductivity is in the order of 1.25 × 10 −2 S cm −1 , which was lower than that of pentacene films doped either with iodine or bromine reported in the literature (electrical conductivity of up to 100 S cm −1 ) [32,33]. Different film thickness, doping concentration and doping method might be reasons for this low value.…”
Section: Molecular Glasses Based Solid State Dsscsmentioning
confidence: 65%
“…Pentacene consists of stacked molecular layers arranged in a herringbone structure with interplanar spacing d 0 0 1 = 14.1 Å [33]. Van der Waals forces are effective between its molecular layers [34,35]. Several techniques, such as photoelectron emission microscopy (PES) [36], potential imaging mapping [37], and scanning Kelvin probe microscopy (SKPM) [38,39] have been used to probe local defects originating from structural disorders, crystalline domain size, shape, and height of the pentacene layer itself.…”
Section: Introductionmentioning
confidence: 99%